2018
DOI: 10.12659/msm.906018
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Alternating Inflatable Head Pad inPatients Undergoing Open Heart Surgery

Abstract: BackgroundPreoperative symptoms like occipital pressure ulcers and alopecia areata (AA) significantly lowered patient quality of life. Therefore, preoperative nursing was in need of investigation. This study aimed to compare effects of an alternating inflatable head pad and a gel pad on occurrence of postoperative pressure ulcers and AA in patients undergoing open heart surgery.Material/MethodsThis was a prospective study. We allocated randomly 120 patients undergoing surgery (3–7 h) in the Yantai Yuhuangding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…Studies on devices to assist in the prevention of occipital PIs are scarce. The few studies undertaken have included air pads, gel pads, or foam rings . Some occipital devices, particularly ring‐shaped or donut‐shaped devices that off‐load the centre of the occiput, have been found to cause more shear at the surface and internally, and in fact increase the risk for the development of PIs .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on devices to assist in the prevention of occipital PIs are scarce. The few studies undertaken have included air pads, gel pads, or foam rings . Some occipital devices, particularly ring‐shaped or donut‐shaped devices that off‐load the centre of the occiput, have been found to cause more shear at the surface and internally, and in fact increase the risk for the development of PIs .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of case reports of pressure alopecia have been observed following extended surgical procedures, giving rise to the alternative name of postoperative alopecia (Abel and Lewis, 1960; Bagaria and Luck, 2015; Chang et al, 2016; Domínguez-Auñón et al, 2004; Huang et al, 2018; Iwai et al, 2009; Lawson et al, 1976; Matsushita et al, 2011; Wiles and Hansen, 1985). Other causes of pressure alopecia reported in the literature include electroencephalogram electrodes (Kunapareddy et al, 2018; Morris et al, 1992), headbands (Sano et al, 2018), fixed head positioning while watching television (Thiem et al, 2016) and breakdancing (Bonifazi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Lawson et al (1976) found that perioperative rotation of the head every 30 min reduced risk of pressure alopecia from 14% to 1%. A prospective study performed by Huang et al (2018) showed that using an alternating inflating head pad during open heart surgery significantly lowered incidence of postoperative alopecia compared to a conventional gel head pad.…”
Section: Discussionmentioning
confidence: 99%
“…Já no estudo de Nixon et al (1998), dos 65 pacientes com LPP, 56 (86%) apresentaram lesões classificadas em Grau 1 (hiperemia com branqueamento), quatro (6,2%) em Grau 2a (hiperemia sem branqueamento) e cinco (7,7%) em Grau 2b (dano superficial na epiderme). Porém, os autores utilizaram para o estadiamento das lesões uma escala modificada de Torrance, diferentemente dos demais estudos incluídos nesta revisão, nos quais as classificações empregadas foram pautadas na Discussão diretrizes da EPUAP e da National Pressure Ulcer Advisory Panel (NPUAP) vigentes na época da condução das pesquisas (HOSHOWSKY;SCHRAMM, 1994;ARONOVITCH et al, 1999;SCHULTZ et al, 1999;RUSSELL;LICHTENSTEIN, 2000;FEUCHTINGER et al, 2006;WU et al, 2011;ZHU;QU, 2018;JOSEPH et al, 2019;EZEAMUZIE et al, 2019).…”
Section: Discussionunclassified
“…6.2 Comparação entre as superfícies de suporte de alta tecnologia com as superfícies de baixa tecnologia Nesta categoria foram incluídos três ensaios clínicos randomizados (ARONOVITCH et al, 1999;RUSSEL;LICHTENSTEIN, 2000;ZHU;QU, 2018) e dois estudos não randomizados (EZEAMUZIE et al, 2019;JOSEPH et al, 2019), nos quais os autores testaram superfícies de suporte de alta tecnologia comparadas as superfícies de baixa tecnologia. Em um estudo primário, os estudiosos indicaram que para o grupo controle o cuidado padrão foi empregado, sem especificar o dispositivo utilizado (JOSEPH et al, 2019).…”
Section: Discussionunclassified